# Yahoo Web Search

related to: A.N.J

1. ### Suppose x is an accumulation point of { a _ n : n in J }. Show that there is a subsequence of { a _ n } that converges?

I'll write S instead of { a _ n : n in J }. If x is an accumulation point of a set...it is in S, it is of the form a _ n _k, and since it is in B_ε(x) it ...

1 Answers · Science & Mathematics · 28/01/2011

2. ### PreCalculus - Binomial Theorem: Find the coefficient of x^8 in the expansion (x^2+3)^7?

Well in this case the formula would be ( n C n - j )* a ^( n - j )*(x^2)^ j x^8 = (x^2)^4 so j = 4 n = 7 n - j = 3 a = 3 So...

2 Answers · Science & Mathematics · 26/07/2009

3. ### math a )--- ( n over J ) not division (186 over 3)?

Your "( n over J )" can be written as " n C J " (standing for...

1 Answers · Science & Mathematics · 22/07/2009

4. ### number theory - modulo?

...gcd( a , n ) = 1. Assume by contradiction that gcd( a ^ j , n ) = d > 1. Then, d | a ^ j and d | n . By... than one. Thus, the assume that gcd( a ^ j , n ) > 1 is false. Therefore, gcd( a ^ j , n ...

2 Answers · Science & Mathematics · 31/10/2011

5. ### can anyone solve this as well?

k + (k+1) + (k+2) + ... + n ??? the answer is ( n -k+1) k + (1 + ... + ( n -k)) = nk - k^2 + k + (( n -k) ( n -k+1)) / 2 = nk - k^2 + k + n ^2/2 - nk + k^2/2 + n /2 - k/2 = ( n ^2 + n - k^2 + k) / 2

1 Answers · Science & Mathematics · 07/01/2010

6. ### A proof for summations?

... left-hand side of the identity can be written (*) ∑ ∑{0 ≤ i ≤ n , 0 ≤ j ≤ n } a _ij b_ij, where b_ij = 1 if (i, j ) is in X and b_ij = 0 otherwise...

1 Answers · Science & Mathematics · 20/05/2014

7. ### Statistics?

... J (NCJ), or in other words, in how many ways can we choose J tags from a group of N . The equation for the combination function is: NCJ = N !/[( J ...

1 Answers · Science & Mathematics · 14/02/2008

8. ### Prove determinant of the Jacobian is non-zero?

Let M = J _f( a ) and N = J _{f^{-1}}(f( a )). Note that M and N ...we learn that NM = J _{f^{-1}}(f( a )) J _f( a ) = J _{f^{-1} o f} ( a ) But...

2 Answers · Science & Mathematics · 20/03/2012

9. ### Solve: x2 + 2(1 + j )x + 2 = 0.?

x's=[-1- j +&-(1+ j ^2+2j-2)^1/2]=-1- j +&-(2j-2)^1/2 God bless you.

1 Answers · Science & Mathematics · 18/12/2012

10. ### Formulas:Solve each formula in terms of the given variable?

Hi, 1. ad=f; a .f --- = a <==ANSWER d 2. n +3=q; n n = q - 3 <==ANSWER 3. 2( j +k)=m;k 2j + 2k = m 2k = m - 2j m - 2j --------- = k <==ANSWER...

6 Answers · Science & Mathematics · 06/10/2008